2013
DOI: 10.3892/etm.2013.1235
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective and immunoregulatory capacity of ginsenoside Rg1 in chronic ultraviolet B-irradiated BALB/c mouse skin

Abstract: The aim of this study was to investigate the photoprotective and immunoregulatory capacities of ginsenoside Rg1 in skin irradiated by chronic ultraviolet B (UVB) and to verify the potential mechanisms of action. BALB/c mice were pretreated with a topical application of ginsenoside Rg1 and irradiated with different doses of UVB daily for 30 consecutive days. Following chronic UVB irradiation, there were significant pathological changes in the skin of the BALB/c mice, including hyperkeratosis, acanthosis, sponge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Supporting our results, naringenin treatment reduces the TNF-α, IL-1β, and IL-6 levels in an ulcerative colitis model in rats, IFN-γ production in an atopic dermatitis mouse model, Th2 cytokine production (IL-4, IL-5, IL-13) in a murine allergic asthma model, IL-17 levels in murine colitis, IL-23 levels in a human osteoclastogenesis model, TNF-α, IL-1β, IL-6, and IL-10 levels in Chlamydia trachomatis -induced inflammation, and TGF-β expression in nephrotoxicity in mice . The release of these cytokines plays a central role in the recruitment and activation of inflammatory cells, leading to skin damage after UVB exposure. ,,,, Moreover, the inhibition of these cytokines is considered a therapeutic approach to control skin cancer progression and metastasis, psoriasis, contact dermatitis, and other diseases. ,,, It is likely that the inhibition of cytokine production by naringenin might be related to the inhibition of early inflammatory events such as inhibition of production or effects of ROS and NF-κB activation.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Supporting our results, naringenin treatment reduces the TNF-α, IL-1β, and IL-6 levels in an ulcerative colitis model in rats, IFN-γ production in an atopic dermatitis mouse model, Th2 cytokine production (IL-4, IL-5, IL-13) in a murine allergic asthma model, IL-17 levels in murine colitis, IL-23 levels in a human osteoclastogenesis model, TNF-α, IL-1β, IL-6, and IL-10 levels in Chlamydia trachomatis -induced inflammation, and TGF-β expression in nephrotoxicity in mice . The release of these cytokines plays a central role in the recruitment and activation of inflammatory cells, leading to skin damage after UVB exposure. ,,,, Moreover, the inhibition of these cytokines is considered a therapeutic approach to control skin cancer progression and metastasis, psoriasis, contact dermatitis, and other diseases. ,,, It is likely that the inhibition of cytokine production by naringenin might be related to the inhibition of early inflammatory events such as inhibition of production or effects of ROS and NF-κB activation.…”
Section: Resultssupporting
confidence: 86%
“…Activation of the NF-κB pathway by UVB irradiation contributes to skin damage, photoaging, and skin tumor formation . Furthermore, UVB irradiation induces the production of multiple cytokines, including TNF-α, ,, IL-1β, , IL-6, , interferon gamma (IFN-γ), , IL-12, IL-4, IL-5, IL-17, IL-23, IL-10, , and transforming growth factor beta (TGF-β) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, Bcl-2 has a positive significance in maintaining cellular 'metabolism'. However, excessive UV radiation or the repeated accumulation of small doses of UV radiation may lead to extensive apoptosis and further induce the occurrence of cataracts (26,27). Therefore, the role of Bcl-2 in apoptosis appears to be a contradictory with negative and positive aspects.…”
Section: Discussionmentioning
confidence: 99%
“…1A) by gastric fluids and the intestinal microflora (1). Previous studies have demonstrated the beneficial effects of ginsenosides and their metabolites on skin health, such as their wound healing (2,3) and anti-aging effects (4,5), as well as protective effects against untraviolet irradiation (6)(7)(8). Pharmacologically, 20GPPD has anti-inflammatory properties (9), anti-aging effects and promotes skin wound healing (5,10).…”
Section: Introductionmentioning
confidence: 99%